Outcomes of the Pedicled Medial Sural Artery Perforator Flap for Soft Tissue Reconstruction Around the Knee: When to Use It and How to Look After It - Narayan, Nitisha; Berner, Juan Enrique; Saeed, Ayman; Zanchetta, Francesco; Troisi, Luigi (Journal of Hand and Microsurgery, 2020)
Introduction The medial gastrocnemius flap is an established workhorse flap to cover proximal leg defects due to its reliability and simplicity to raise. However, it has the disadvantage of being bulky, requiring a skin graft for coverage, and is associated with loss of muscle power. The pedicled medial sural artery perforator (MSAP) flap has gained popularity as a reconstructive alternative for defects of the lower extremities. We present a case series of pedicled MSAP flaps for reconstructing defects around the knee as an alternative to the medial gastrocnemius flap.Materials and Methods A consecutive series of patients with proximal leg defects following trauma, osteomyelitis, burns, and chronic wounds were included. A hand-held Doppler was used to map out the MSAPs. Defects were reconstructed using pedicled MSAP flaps, preserving the nerve supply to the gastrocnemius muscle. Patient outcomes were recorded, including their Enneking scores postreconstruction.Results A total of 10 pedicled flaps was performed to reconstruct defects around the knee joint between October 2017 and November 2018. All the patients were discharged 1 week postoperatively, and rehabilitation consisted of graduated flexion in a knee brace by means of controlled passive mobilization. Three out of the ten patients developed complications: one patient developed flap congestion, one developed epidermolysis of the tip of the flap, and the other patient had partial necrosis of the skin paddle. The average Enneking score was 29 out of 35.Conclusion The pedicled MSAP flap is a good reconstructive option for proximal leg defects as it is associated with lower donor site morbidity and provides an aesthetically pleasing reconstruction.
Keywords: knee; medial sural artery perforator; flaps; soft tissue reconstruction